Hubungan Pengetahuan Ibu Dan Praktik Pemberian MP-ASI Dengan Perkembangan Bayi Usia 6-12 Bulan Di Wilayah Puskesmas Kassi-Kassi Kota Makassar (Window of Public Health Journal, 2026)
Maternal knowledge of nutrition and complementary feeding practices plays an essential role in supporting appropriate infant feeding. However, many mothers still lack adequate understanding of recommended complementary feeding (MP-ASI), which may affect infant development, particularly gross and fine motor skills that develop rapidly during the first year of life. This study aimed to examine the relationship between maternal knowledge and complementary feeding practices with infant motor development among infants aged 6–12 months in the working area of the Puskesmas Kassi-Kassi. This study employed a quantitative cross-sectional design. A total of 134 mothers with infants aged 6–12 months were selected using purposive sampling. Data were collected using a maternal knowledge questionnaire on MP-ASI, a complementary feeding practices questionnaire, and the Developmental Pre-Screening Questionnaire (KPSP) to assess gross and fine motor development. The results showed no significant association between maternal knowledge and infant motor development, both fine and gross motor skills (p = 1.000). Similarly, complementary feeding practices were not significantly associated with fine motor development (p = 0.479) or gross motor development (p = 0.671). In conclusion, maternal knowledge and complementary feeding practices were not identified as determining factors for motor development in this study. These findings suggest that infant motor development may be more strongly influenced by other factors, such as stimulation, caregiving environment, and overall child health. Therefore, health education programs should emphasize not only nutritional knowledge but also parental engagement and stimulation strategies to support optimal motor development.